Bacterial noncoding Y RNAs are widespread and mimic tRNAs - Chen, Xinguo (Cold Spring Harbor Laboratory Press, 2014)
Many bacteria encode an ortholog of the Ro60 autoantigen, a ring-shaped protein that is bound in animal cells to noncoding RNAs (ncRNAs) called Y RNAs. Studies in Deinococcus radiodurans revealed that Y RNA tethers Ro60 to polynucleotide phosphorylase, specializing this exoribonuclease for structured RNA degradation. Although Ro60 orthologs are present in a wide range of bacteria, Y RNAs have been detected in only two species, making it unclear whether these ncRNAs are common Ro60 partners in bacteria. In this study, we report that likely Y RNAs are encoded near Ro60 in >250 bacterial and phage species. By comparing conserved features, we discovered that at least one Y RNA in each species contains a domain resembling tRNA. We show that these RNAs contain nucleotide modifications characteristic of tRNA and are substrates for several enzymes that recognize tRNAs. Our studies confirm the importance of Y RNAs in bacterial physiology and identify a new class of ncRNAs that mimic tRNA.